Propuesta arquitectónica de centro de rehabilitación de drogas utilizando contenedores marítimos para el cantón San Lorenzo, Esmeraldas - Gruezo Tipán, Jessie Yuranis (2024)
In Ecuador, there has been a remarkable surge in drug consumption. This escalating issue stems from the inadequacy of rehabilitation centers in meeting the needs of individuals struggling with drug dependence. Hence, the proposal of establishing a Drug Rehabilitation Center in the town of San Lorenzo in the province of Esmeraldas, an area that is notably afflicted and lacks suitable facilities for addressing the challenges of addiction. This initiative involves the utilization of sustainable construction methods through the recycling of maritime containers. These containers possess advantageous features such as cost-effectiveness, resilience, robustness, and longevity. Such constructions are aptly termed as Cargotecture, representing a novel approach to creation and construction. The design of the current proposal takes into account various design aspects............